PENGARUH PEMBERIAN LIMBAH CAIR INDUSTRI TEMPE DAN MIKORIZA TERHADAP KETERSEDIAAN HARA N DAN P SERTA PRODUKSI JAGUNG (Zea mays L.) PADA TANAH INCEPTISOL - Muhammad Riza Hapiza; T. Sabrina; Posma Marbun (Universitas Sumatera Utara, 2014)
Tempe industry liquid waste contains several nutrients that can be absorbed by plant roots.Application of mycorrhiza with tempe industry liquid waste to maize simultaneously planted onInceptisol is expected to increase nitrogen and phosphate available. The aim of this study was toexamine the best concentration of tempe industry liquid waste and mycorrhiza dosage in increasingN and P availability in Inceptisol soil and maize producion. The experiment was conducted in theexperimental fields of the Faculty of Agriculture USU ( ± 25 m asl) from March - July 2013 andusing a randomized block design (RBD) with 2 factors and 3 replications. The first factor wasconcentration of liquid tempe industry waste (0, 20, 40 and 60 mL of tempe industry liquid wastetempe/100 mL of water) and the second factor was mycorrhiza dosage (0, 10 and 20gmycorrhiza/plant). The results showed that the tempe industry liquid waste increased the root dryweight of maize significantly. Application mycorrhiza affected the concentration of N on leafsignificantly. The tempe industry liquid waste and mycorrhiza and its interaction were notsignificant effect on the parameters of the soil pH, C-organic, total-N soil, uptake of N, P-available,the concentration of P on leaf, uptake of P, population of microorganisms,degree of mycorrhizainfection, canopy dry weight of maize, weight of cobs, plant height and stem diameter. The bestconcentration of tempe industry liquid waste was 60% which increased the cob weight of themaize 1.15 to 1.25 times higher than the weight of cobs on the others concentration of tempeindustry liquid waste or without application of tempe industry liquid waste.Keywords : tempe industry liquid waste, mycorrhiza, the availability of N , the availability of P, theproduction of corn .